2011
DOI: 10.1111/j.1573-7861.2010.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Economic Performance in American Metropolitan Areas: An Empirical Investigation1

Abstract: This article exploits differences in the Gay Index representing diversity and tolerance to estimate the effect of talent on economic performance in U.S. metropolitan areas, and proposes a theory of mechanism of talent distribution and its economic consequences. The index shows there were different degrees of tolerance in early years in different metropolitan areas, with different associated talent. Areas that had high tolerance in early years are more likely tolerant and diverse currently, and can attract more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Reflecting the heavy influence of U.S. records, the most common area unit was the census tract, which was used in 13 records [ 68 , 73 , 76 , 77 , 79 – 83 , 89 , 90 , 92 , 93 ]. The second most common area unit was the Metropolitan Statistical Area (MSA) used in 11 records [ 13 , 28 , 32 , 71 , 72 , 74 , 84 , 85 , 88 , 91 , 95 ]. Five records used cities or U.S. census places [ 31 , 56 , 61 , 67 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reflecting the heavy influence of U.S. records, the most common area unit was the census tract, which was used in 13 records [ 68 , 73 , 76 , 77 , 79 – 83 , 89 , 90 , 92 , 93 ]. The second most common area unit was the Metropolitan Statistical Area (MSA) used in 11 records [ 13 , 28 , 32 , 71 , 72 , 74 , 84 , 85 , 88 , 91 , 95 ]. Five records used cities or U.S. census places [ 31 , 56 , 61 , 67 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, corporate sexual equality policies help recruit productive employees. Just like cities more open and tolerant towards different sexual orientations tend to attract more knowledgeable workers who in return boost the local economy (Chen, ; Florida, ; Fu, ), a supportive organization culture helps attract and recruit high‐quality job applicants (Backhaus et al ., ; Catanzaro, Moore, and Marshall, ). Non‐discrimination practices in terms of sexuality can create a more open, diverse, tolerant and supportive environment for employees, and therefore can help recruit talented and productive employees.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Beyond their theoretical implications, the findings have troubling implications for the future of low‐income areas in the United States. Airports play an important role in attracting talent and places with high levels of talent/highly educated individuals enjoy robust economic growth and high productivity (Chen, ; Florida, ; McGranahan et al., ; Rauch, ). Places without access to airports experience a deepening brain drain—more talent moving out and less moving in—and the advantages associated with human capital concentration flow disproportionately to those places with high centrality positions in the airport traffic network (i.e., hub city).…”
Section: Discussionmentioning
confidence: 99%
“…Florida () confirmed that talent is a key intermediate variable in attracting high‐technology industries and generating higher regional incomes. Recent evidence supporting the relationship between human capital and regional development can be found in different disciplines (e.g., Chen, ; Gennaioli et al., ; Lengyel and Ságvári, ; Florida et al., ; McGranahan et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation